2004
DOI: 10.1097/01.brs.0000109763.77854.9b
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Flap Valve Presenting as Neurogenic Claudication

Abstract: We report a case that was diagnosed as neurogenic claudication on clinical features and MRI evidence. However, subsequent to an aortogram the diagnosis was revised. Intermittent claudication is often difficult to distinguish from neurogenic claudication. There are no sensitive discriminators based on history alone. In the presence of poor or absent peripheral pulses, an arteriogram is necessary to ascertain the relative importance of the peripheral arterial circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The final studies included were case reports or series. Eighteen reports referred to abdominal conditions that mimic spinal diseases ( Table 1 ), 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 among them a patient with cyclic lumbar back pain who received a lumbar spinal fusion who, after persisting symptoms led to further diagnostic procedures, was ultimately diagnosed with endometriosis. 15 Spinal symptoms included paraplegia and urinary incontinence as results of acute aortic pathologies.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…The final studies included were case reports or series. Eighteen reports referred to abdominal conditions that mimic spinal diseases ( Table 1 ), 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 among them a patient with cyclic lumbar back pain who received a lumbar spinal fusion who, after persisting symptoms led to further diagnostic procedures, was ultimately diagnosed with endometriosis. 15 Spinal symptoms included paraplegia and urinary incontinence as results of acute aortic pathologies.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…This result is very close to the result previously observed with post-exercise ABI, and supports the use of tcpO2 in the present study. Claudication resulting from isolated proximal-without-distal RBFI is rarely reported in the general population, found as only isolated observations or very small series (22,23). Previous reports have demonstrated that isolated proximal ischemia can mimic symptoms of neurological or musculoskeletal origin (22,24) and may result in isolated distal symptoms in approximately 15% of the cases (25).…”
Section: Overall Prevalence Of Positive Tests and Isolated Proximal Rfbimentioning
confidence: 99%